Time is crucial in malignant tumor cases: Speeding up the process of patient-specific implant creation - Spalthoff, Simon; Nejati-Rad, Narin; Rahlf, Björn; Jehn, Philipp; Gellrich, Nils-Claudius; Lentge, Fritjof; Korn, Philippe (Frontiers in Oncology, 2022)
Purpose Patient-specific implants are commonly used to reconstruct lower jaw defects following surgical treatment for head and neck squamous cell carcinoma. The planning process of surgery is time-consuming and can delay the “time to surgery,” which should be as short as possible. Therefore, this study aimed to evaluate the planning process to speed up and identify any sources of problems. Patients and methods In this retrospective study, we enrolled patients who underwent continuous resection of the mandible in combination with reconstruction with a patient-specific implant between 2016 and 2021. The predictor variables were in-house training of the engineers and implant complexity (complex [with additional features] vs. less complex [resembling standard reconstruction plates]). The outcome variables were the duration of communication, message length, and the need for synchronous communication or modifications to the original design. Descriptive and univariate statistics were computed, and statistical significance was set at P < 0.05. Results The data from 83 patients were included in this study. The mean duration of communication was 14.05 ± 13.58 days. The implant complexity and training status of the engineer had no statistically significant influence on the primary outcome variables. As for the secondary outcome variables, the implant complexity significantly influenced the chance that the planned operation had to be postponed (15/16 [93.75%] were complex cases, P = 0.001). The most frequent cause of problems in the planning process was an insufficient dataset, which was not dependent on the type of imaging. Conclusions The overall duration of the patient-specific implant creation process is too long to meet oncological requirements. Therefore, standardization of the planning process to accelerate implant creation is of utmost importance. In addition, a common standard imaging format (independent of the type of imaging) for oncological cases could eliminate all delays caused by insufficient datasets in the future.